Global evaluation of Musa germplasm for resistance to fusarium wilt, Mycosphaerella leaf spot diseases and nematodes: in-depth evaluation - Carlier, J.; Waele, D. de; Escalant, J-V.; Vézina, A.; Picq, C.; International Network for the Improvement of Banana and Plantain (2002)
This technical guidelines replaces technical guidelines 1 ('Screening of Musa Germplasm for resistance and tolerance to nematodes') and 3 ('Evaluation of Musa germplasm for resistance to Sigatoka diseases and Fusarium wilt') as far as indepth evaluations are concerned. Technical Guidelines for performance evaluations, which were also part of Technical guidelines 3, will appear shortly. These changes were made to reflect the apparition of a third disease caused by a Mycosphaerella fungus ('eumusae leaf spot disease'), to simplify the guidelines, and to group under one cover the evaluations for the main pests and diseases affecting bananas. These guidelines have been written with the collaboration of the Fusarium, Sigatoka and Nematology working groups of PROMUSA and INIBAP staff with the objective of helping researchers to design their trial, choose the appropriate location for the trial, and evaluate selected genotypes for resistance and tolerance to various diseases. Field forms are included to hel data collection.